Case report: Assessing COVID-19 transmission in professional volleyball in Germany, September to December 2020: An epidemiological study - Morath, O.; Barsch, F.; Lazaro, A.; Huzly, D.; Deibert, P. (Frontiers in Sports and Active Living, 2022)
Introduction: The SARS-CoV-2 pandemic poses extraordinary challenges in all fields of daily life. The WHO recommended social distancing guidelines and person-to-person contact was strongly discouraged to contain transmission. Team-based sports were questioned and widely debated. However, there is a lack of available evidence on the risk of in-game SARS-CoV-2 transmission. We aim to derive new insights regarding the risk of SARS-CoV2 infection during team sports and provide current opinion on how to behave during training and competition.